A revision of the subgenus Pedionis (Pedionis) Hamilton from China, with description of two new species (Hemiptera: Cicadellidae) - Zhang, Bin; Zhang, Ruiling (Zootaxa, 2014)
Twenty species of the subgenus Pedionis occurring in the Chinese fauna are recognized, including two new species, P. aculeata sp. nov., P. papillata sp. nov. from Guizhou Prov., China. And, P. nankunshanensis Li, Dai & Li, 2011 is here considered as a junior synonym of P. yunnana Zhang & Viraktamath, 2010. A key to Chinese species of subgenus Pedionis is also provided as well as a checklist.